2016
DOI: 10.5539/mas.v10n11p211
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Machinery and Special Scheme of Inspection’s Requirement towards Industry Competitiveness in Malaysia

Abstract: The amendment of the Factories and Machinery Act 1967 (FMA) in 2006, with the inclusion of the new provision on special scheme of inspection takes into account of the development and advancement of technology, particularly on the latest procedure of inspection of plant and machinery in the Malaysian industries. The FMA since 1967 is the safety at work legislation applicable in Malaysia that provides for the control of factories with respect to matters relating to safety, health and welfare of person therein, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…In that paper, it has been demonstrated that the application of RBI plans for four fixed offshore structures had led to a reduction of one to several million US$ in the total expected cost of inspection. The finding of seems to share the same opinion as they reported that RBI provides economic benefits in terms of fewer inspections, a minimum duration of shutdowns, longer run length, and less frequent shutdowns. Ref.…”
Section: Benefits Of Implementing Rbi Approachsupporting
confidence: 63%
See 2 more Smart Citations
“…In that paper, it has been demonstrated that the application of RBI plans for four fixed offshore structures had led to a reduction of one to several million US$ in the total expected cost of inspection. The finding of seems to share the same opinion as they reported that RBI provides economic benefits in terms of fewer inspections, a minimum duration of shutdowns, longer run length, and less frequent shutdowns. Ref.…”
Section: Benefits Of Implementing Rbi Approachsupporting
confidence: 63%
“…They are: (a) RBI is a cost‐effective program; (b) RBI would increase the effectiveness and profitability of the business; (c) RBI is a safe operation; (d) RBI is an environmentally friendly operation; (e) RBI could increase reliability of process machinery; and (f) RBI is easy to manage. These benefits are established based on the benefits reported in the literature review , , . Items (a), (b), (c), and (d) are market‐related benefits, while items (e) and (f) are benefits related to effective operation and improvement of internal procedures.…”
Section: Results Of the Studymentioning
confidence: 99%
See 1 more Smart Citation